1985
DOI: 10.1346/ccmn.1985.0330413
|View full text |Cite
|
Sign up to set email alerts
|

Hydration States of Interlamellar Chromium Ions in Montmorillonite

Abstract: Abstraet--Hydroxychromium montmorillonites were prepared from solutions containing chromium nitrate and varying amounts of NaOH. The reactant Cr ions were hydrolyzed and, in some experiments, were dimerized to a significant extent. The extent of polymerization in the product formed from a solution containing a maximum amount of [Cr2(H20)s(OH)2] a+ was compared with that in products obtained from solutions containing monomer, [Cr(H20)5OH] 2 § and lesser amounts of the dimer. Despite the uncertainty about the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…Additional evidence for the inner-sphere complexation of Cr is found in the work of Carr (1985), which revealed the surface-catalysed polymerization of intercalated hydroxy-Cr oligomers. Hydrolytic polymerization of Cr(III) requires the replacement of H20 with OH-within the coordination sphere of Cr(III).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Additional evidence for the inner-sphere complexation of Cr is found in the work of Carr (1985), which revealed the surface-catalysed polymerization of intercalated hydroxy-Cr oligomers. Hydrolytic polymerization of Cr(III) requires the replacement of H20 with OH-within the coordination sphere of Cr(III).…”
mentioning
confidence: 80%
“…The adsorption of various heavy metals by smectites has received considerable attention in the past. The adsorption of Cd (Egozy, 1980;lnskeep & Baham, 1983;Van Bladel et al, 1993), Co (Egozy, 1980), Cr (Rengasamy & Oades, 1978;Brindley & Yamanaka, 1979;Carr, 1985;Dubbin et aI., 1994), Cu (Inskeep & Baham, 1983), Hg (Blatter, 1973), Pb (Griffin & Au, 1977), and Zn (Asher & Bar-Yosef, 1982;Van Bladel et al, 1993) are among those metats that have received the most attention. Most of the above-mentioned work, however, has focused only on equilibrium studies or adsorption mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have also been successful in producing hydroxy interlayers of A1 (Rich, 1968;Goh and Huang, 1986;Barnhisel and Bertsch, 1989), Fe (Carstea et al, 1970;Martin-Luengo et al, 1989), Zr , Ni (Yamanaka and Brindley, 1978), and Cr Carr, 1985). The hydroxy-Cr interlayered montmorillonite prepared by Brindley and Yamanaka (1979) displayed a basal spacing near 16.8/~, considerably larger than the 14.4/~ spacing of chlorite.…”
Section: Introductionmentioning
confidence: 99%
“…These workers were unable to determine the structure of the hydroxy-Cr polymers. While studying hydration states of interlamellar Cr in montmorillonite, Carr (1985) observed that the interlayer region catalyzed the formation of larger hydroxyCr polymers. The first-order reflections of the interlayered clays varied from 10 ~k to 15 ~ and tended to be broad, indicating variable basal spacings.…”
Section: Introductionmentioning
confidence: 99%